The relationship between top-down attentional control and changes in weight. (August 2015) - Hotham, Sarah; Sharma, Dinkar
Abstract: Aim: To investigate the relationship between top-down attentional control in the presence of food cues and weight change over a 3-month period. Method: A Stroop task adapted to include background images of high-fat food and neutral items was completed by participants (N = 60). Top-down attentional control was assessed by adaptation effects (Stroop effect is smaller when the previous trial is incongruent). To assess weight change, measurements were taken immediately after the Stroop task (T1) and again 3-months later (T2). Differences in weight between T1 and T2 were calculated and three groups formed: weight gain (n = 20); weight loss (n = 20); and no change in weight (n = 20). Results: Differences in top-down attentional control were observed according to weight change. Participants who demonstrated reduced top-down attentional control also exhibited changes in weight (both loss and gain) over the 3-months. In contrast, the weight of participants who maintained top-down attentional control in the Stroop task remained stable. Conclusions: Findings suggest that attentional control may have a role to play in actual eating behavior. Individuals who demonstrated reduced levels across of top-down attentional control also experienced changes in their weight over the 3-month period. Whether individuals lost or gained weight attentional control was reduced. This reduction was, however, not specific to high-fat food cues, but a general reduction in attentional control across both image conditions. Highlights: Reduced attentional control in the Stroop task was related to weight change. Individuals who lost or gained weight demonstrated reduced attentional control. Reduction was across both image types and not specific to food cues. No change in weight was observed for individuals who maintained attentional control.